2014
DOI: 10.2134/agronj14.0152
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Agent Influence on Water Infiltration into Hydrophobic Sand: I. Rewettability

Abstract: Soil water repellency causes non-uniform water in ltration at slow ow rates, which leads to localized dry spot (LDS) on golf course putting greens. Wetting agents are the primary tool used to reduce soil water repellency on golf courses. Field experiments evaluating the e cacy of wetting agents o en result in inconsistent conclusions due to variable environmental conditions, management intensity, and level of hydrophobicity. is study used octadecylamine treated sand, which exhibits stable and consistent water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Some reports show enhanced soil water retention and increased water holding capacity compared with untreated material without improved water movement in water repellent soil [ 35 , 36 ]. In contrast, others found improved water infiltration/drainage or lower soil water content in treated hydrophobic soil [ 37 , 38 , 39 , 40 , 41 ]. These results suggest that wetting agents with different chemical properties may act through different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports show enhanced soil water retention and increased water holding capacity compared with untreated material without improved water movement in water repellent soil [ 35 , 36 ]. In contrast, others found improved water infiltration/drainage or lower soil water content in treated hydrophobic soil [ 37 , 38 , 39 , 40 , 41 ]. These results suggest that wetting agents with different chemical properties may act through different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high affinity among nonpolar structures, once wetting agents are watered in through irrigation/precipitation, these amphiphilic surfactants attach their nonpolar tails onto nonpolar hydrophobic surfaces, and subsequently increase the overall soil wettability by facing the polar heads toward the by-passing water (Cisar et al, 2000;Dekker et al, 2005;Kostka, 2000). Addition of wetting agents can hence reduce the surface tension of water from 73 to 32 mN m -1 or lower depending on the wetting agent selected and rate used, ultimately facilitating spontaneous wetting and water infiltration into hydrophobic sand (Song et al, 2014a). This effect, however, diminishes over time as the wetting agent molecules degrade, and often repeat applications are needed to maintain soil wettability year-round (Song et al, 2014b).…”
mentioning
confidence: 99%
“…These results indicated a superior effect of AE, ABP, and PoAP for SWR mitigation, compared to other wetting agents included in this experiment. Previous research reported that hydrophobic sands treated with certain wetting agents, such as AE, maintained their wettability for an extended period, compared with other compounds such as PXL [28]. Table 2.…”
Section: Soil Vwc Lds and Swrmentioning
confidence: 99%